SEXUAL VIOLENCE SURVIVOR RESISTANCE: RECLAIMING SAFE SPACES FOR SANTRIWATI IN PESANTREN - Komala, Ajeng Ratna; Fajriyah, Iklilah Muzayyanah Dini (EGALITA, 2025)
Abstract The persistent occurrence of gender-based sexual violence within Indonesian pesantren (Islamic boarding schools) demands urgent academic scrutiny, particularly due to its underreported nature and the complex power dynamics embedded within their exclusive and autonomous educational structures. While existing scholarship has primarily centered on the causes and prevention of sexual violence in these institutions, the lived experiences, agency, and resistance strategies of survivors remain critically underexplored. Addressing this gap, the present study investigates how survivors within pesantren contexts navigate their transformation from perceived powerless victims to active agents of resistance. Specifically, it examines the sociocultural barriers they encounter, the forms of resistance they employ, and the broader implications of their defiance. Employing a qualitative literature review methodology, this research synthesizes insights from 20 relevant studies—7 focused on pesantren in Indonesia and 14 international studies on survivor resistance. Thematic analysis was conducted, with data interpreted through the lenses of radical feminist theory and agency theory, focusing on female representation in pesantren and survivor-driven resistance. Findings indicate that, despite the deeply patriarchal and feudal systems that characterize many pesantren, survivors assert agency through diverse strategies—ranging from personal resilience and storytelling to legal advocacy and collective mobilization. These acts of resistance not only challenge systemic silencing but also contribute meaningfully to shifts in public discourse and legal accountability. This study contributes a critical perspective to gender and Islamic education scholarship by centering survivor agency and offering pathways for transformative justice within religious educational settings. Keywords: Resistance; Survivors; Sexual Violence; Pesantren; Santriwati.Abstrak Kasus kekerasan seksual berbasis gender yang terus terjadi di lingkungan pesantren di Indonesia menuntut perhatian akademik yang mendesak, terutama karena sifatnya yang jarang dilaporkan serta dinamika kekuasaan yang kompleks dalam struktur pendidikan yang eksklusif dan otonom. Meskipun sejumlah penelitian telah menyoroti penyebab dan upaya pencegahan kekerasan seksual di pesantren, pengalaman hidup, agensi, dan strategi perlawanan para penyintas masih sangat minim dieksplorasi. Untuk mengisi kekosongan ini, studi ini menelusuri bagaimana para penyintas di lingkungan pesantren membangun transformasi dari korban yang dipersepsikan tidak berdaya menjadi subjek aktif yang melawan. Secara khusus, penelitian ini mengkaji hambatan sosial dan kultural yang mereka hadapi, bentuk-bentuk perlawanan yang mereka lakukan, serta dampak yang lebih luas dari tindakan perlawanan tersebut. Dengan menggunakan metode tinjauan pustaka kualitatif, penelitian ini mensintesis temuan dari 20 studi relevan—7 di antaranya berfokus pada konteks pesantren di Indonesia dan 14 studi internasional tentang perlawanan penyintas. Analisis tematik dilakukan dengan menggunakan kerangka teori feminis radikal dan teori agensi, dengan fokus pada representasi perempuan dalam pesantren dan resistensi yang digerakkan oleh penyintas. Temuan menunjukkan bahwa, meskipun sistem patriarkal dan feodal sangat mengakar dalam banyak pesantren, para penyintas menunjukkan agensi melalui berbagai strategi—mulai dari ketahanan pribadi dan narasi pengalaman, hingga advokasi hukum dan mobilisasi kolektif. Tindakan perlawanan ini tidak hanya menantang pembungkaman sistemik, tetapi juga memberikan kontribusi signifikan terhadap perubahan wacana publik dan akuntabilitas hukum. Studi ini menawarkan perspektif kritis dalam kajian gender dan pendidikan Islam, dengan menekankan agensi penyintas serta membuka jalan bagi keadilan transformatif dalam lingkungan pendidikan keagamaan. Kata Kunci: Perlawanan; Penyintas; Kekerasan Seksual; Peantren; Santriwati.